The missions of Jesus and the disciples according to the Fourth Gospel with implications for the Fourth Gospel's purpose and the mission of the contemporary church - Kostenberger, Andreas J. 1957- (Grand Rapids, MI Eerdmans, 1998)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. John -- language, style; Greek, Biblical -- semantics; Missions -- theory